Implementation of Inclusive Education of Elementary Schools: a Case Study in Karangmojo Sub-District, Gunungkidul Regency - Nugraheni Dwi Budiarti; Sugito Sugito (Intelektual Pustaka Media Utama, 2018)
This study examined: a) school member interactions that reflect an inclusive culture, b) school policies in promoting inclusion, c) evolving inclusive practies of elementary schools. This study employed the qualitative approach, with case study designs. The research was conducted at 7 Inclusive Inclusice schools in Karangmojo Sub-district. This study reveals that interaction of school members in creating inclusive culture can be seen from their efforts to cultivate mutual respect among the school members, big support and role of the principal in engaging all parties, and partnerships between school, parents, and community. Policies in promoting inclusive education can be seen from the procedures of student admissions that are flexible and non-discriminatory, and the efforts of the school to conduct accessibility of facilities and infrastructure for the children with special needs, regular teacher-special assistant teachers collaboration, as well as the flexibility of curriculum implementation for children with special needs. Evolving inclusive practies can be seen from identification and assessment for students suspected to have special needs, applying the curriculum development for teaching-learning processes, and the provision of school budget allocations for the development of inclusive education both from government funds and private funds.